STERILITY TESTING PROCEDURE OF OPHTHALMIC OCUSERT ACICLOVIR USED FOR TREATING HERPES SIMPLEX VIRUS - S, Shanmugam; S, Valarmathi; Kumars, Satheesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The present work focuses on sterility studies of prepared aciclovir ocusert which is so essential for ophthalmic preparations. According to Indian Pharmacopoeia, the sterility test was performed. Ocuserts are sterile preparations which are placed into cul-de-sac or conjunctival sac. Ophthalmic inserts offer many advantages over conventional dosage forms such as increased ocular residence time, possibility of releasing drugs at a slow and constant rate and accurate dosing. Ocuserts are formulated for treating external ocular diseases such as conjuctivitis, corneal ulcer, and keratoconjuctivitis. Ophthalmic preparations contaminated with microorganisms cause corneal damage and finally blindness, especially if the microorganism is Pseudomonas aeruginosa. Ophthalmic preparations should be manufactured in aseptic condition and to be sterilized before packing. Methods: According to Indian Pharmacopoeia, the official sterility test for ocusert was performed for detecting the presence of microbes. The selected F2 formulation which shows controlled drug release after 24 hrs was selected for the sterility test. The F2 formulation was subjected to ultraviolet radiation for sterilization. The sterilized ocusert and unsterilized ocusert were placed in fluid thioglycollate medium and incubated for 7 days at 20-25oC. Results: After 7 days of incubation, the sterilized ocusert shows no microbial growth and unsterilized ocusert shows microbial growth. The prepared aciclovir ocuserts were found to be sterile after the completion of official sterility test. Conclusion: The sterility studies conclude after 7 days of incubation period; there was no appearance of turbidity which indicates the prepared formulation F2 was found to be sterile.